Cellular resolution anatomical and molecular atlases for prenatal human brains. Issue 1 (29th December 2021) - Ding, Song‐Lin; Royall, Joshua J.; Lesnar, Phil; Facer, Benjamin A.C.; Smith, Kimberly A.; Wei, Yina; Brouner, Kristina; Dalley, Rachel A.; Dee, Nick; Dolbeare, Tim A.; Ebbert, Amanda; Glass, Ian A.; et al.
Abstract: Increasing interest in studies of prenatal human brain development, particularly using new single‐cell genomics and anatomical technologies to create cell atlases, creates a strong need for accurate and detailed anatomical reference atlases. In this study, we present two cellular‐resolution digital anatomical atlases for prenatal human brain at postconceptional weeks (PCW) 15 and 21. Both atlases were annotated on sequential Nissl‐stained sections covering brain‐wide structures on the basis of combined analysis of cytoarchitecture, acetylcholinesterase staining, and an extensive marker gene expression dataset. This high information content dataset allowed reliable and accurate demarcation of developing cortical and subcortical structures and their subdivisions. Furthermore, using the anatomical atlases as a guide, spatial expression of 37 and 5 genes from the brains, respectively, at PCW 15 and 21 was annotated, illustrating reliable marker genes for many developing brain structures. Finally, the present study uncovered several novel developmental features, such as the lack of an outer subventricular zone in the hippocampal formation and entorhinal cortex, and the apparent extension of both cortical (excitatory) and subcortical (inhibitory) progenitors into the prenatal olfactory bulb. These comprehensive atlases provide useful tools for visualization, segmentation, targeting, imaging, and interpretation of brain structures of prenatal human brain, and for guiding and interpreting the next generation of cell census and connectome studies. Abstract : Detailed cellular resolution anatomical atlases are generated for prenatal human brains at postconceptional weeks (PCW) 15 and 21 based on combined analysis of Nissl preparation, acetylcholinesterase staining, and a lot of gene markers. Using the anatomical atlases as a guide, spatial expression of 37 and 5 genes (out of 43 genes) from the brains, respectively, at PCW 15 and 21 was annotated as molecular atlases. These atlases provide useful resource for visualization, segmentation, targeting, imaging, and interpretation of normal and abnormal human brain development.